Negotiating the networks : a study of telework within chartered accountancy firms in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Manawatu Campus, New Zealand - Jones, Leslie David (Massey University, 2017)
Is telework an acceptable work practice among chartered accountancy firms here in Aotearoa New Zealand? Probably not, according to the research by Rasmusson and Corbett (2008), although their research was not specific to chartered accountancy firms. In fact, there have been no specific studies of the acceptance or otherwise of telework by chartered accountancy firms in the New Zealand context. In the international context, North American research suggests that telework is supported by chartered accountancy firms as a way of retaining skilled staff, especially women accountants, because of the feminisation of the profession (Kranz, 2008). On the other hand, Lightbody (2008), in the Australian context disagrees, citing the accountancy culture of work hard, desire for promotion and the need to put the firm first as marginalising accountants who wished to work at home. This thesis, addresses this question in the New Zealand context. Studying only those few chartered accountancy firms that accept telework as a work practice, this thesis asks: What is it about how these firms are organised that allows accounting actors to be located productively in their homes? In answering this question, the directors and managers of the participating firms were interviewed and their resulting stories analysed using a form of analysis drawn from Actor Network Theory, a research framework not previously used by telework researchers. The results of this study show how the traditional networks of the chartered accountancy firm grounded in the office predominate. As a result, the networks of the home have been only marginally successful in intruding into the networks of such firms.
Keywords: Telecommuting; Accounting firms; Accounting; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies